PERSPECTIVA EXTINDERII INTERACŢIUNILOR OM–CALCULATOR: REFLECŢII, SUGESTII - Ulian, Galina; Caprian, Iulia; Maximilian, Silvestru; Caprian, Iurie (CEP USM, 2014)
Dezvoltarea sustenabilă a tuturor activităţilor umane, inclusiv a activităţilor economice, ecologice, poate fi realizatănumai dacă tehnologiile computerizate, pregătirea intelectuală a omului, interacţiunile HUMAN-COMPUTER, limbajul utilizatorilor de tehnologii computerizate se vor înscrie în ecosistem, fără a modifica ecosistemul. Activităţile umane depind în mare măsură de problemele ecologice, energetice, demografice, alimentare la nivel global. Mediul global determină mediul şi problemele la nivel naţional. De aceea, tehnologiile compuerizate în fiecare ţară sunt tratate în contextul trendurilor şi restricţiilor globale.

The sustainable development of all human activities, including economic and ecological activities, can be achieved only if information technologies, human intellectual training, HUMAN-COMPUTER interactions, language of the computer technologies users will be included in the ecosystem, without altering the ecosystem. Human activities depend largely on the environment, energetic, demographic and food issues at the worldwide level. The global environment determines the environment and issues at the national level. Therefore computer technologies in each country are treated in the context of global trends and restrictions.
THE EXTENDENCE OF PERSPECTIVE INTERACTIONS HUMAN-COMPUTER: REFLECTIONS, SUGESTIONS
Keywords: tehnologii computerizate; sisteme economice; cercetător ştiinţific; economic systems; intercommunication